Marketingul pentru sectorul public - Scutaru, Codrin (Calitatea Vieții, 2009)
The hypothesis of the current article is that the marketing could be a form of social innovation for the public sector, a new solution for the frequent problems of this sector in the process of promoting its programs, the necessity and the effects of these programs. The specific take-over of the marketing techniques by the public sector represents a form of social innovation in the sense that through the marketing techniques, a solution is offered to a real problem of the public sector: maintaining the beneficiaries (citizens) well informed and somehow satisfied by the results of the development and the implementation of the programs developed by the public sector.